Implementasi Framework Laravel dalam Pembuatan Website Segitiga Motor dengan Metode Waterfall - Dini Nurul Azizah; Luthfi Dika Chandra; Muhammad Galuh Gumelar; Wien Kuntari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Segitiga Motor website was developed using the Laravel framework with the SDLC Waterfall model approach to digitize the management of customer data and workshop services. The development process includes stages such as requirements analysis, system design, implementation, testing, and maintenance. Laravel was chosen for its ability to speed up development through reusable components and its organized and flexible structure. The website successfully integrates key features such as online service booking, customer data management, product catalog, and promotions, all effectively. Testing results show that the system works as planned, enhancing operational efficiency and making it easier for customers to access services. For future development, adding features like analytics and integration with digital payment systems could further improve customer experience and satisfaction.